Utilizing the Potential of Microorganisms for Managing Arsenic Contamination: A Feasible and Sustainable Approach - Upadhyay, Munish K.; Yadav, Poonam; Shukla, Anurakti; Srivastava, Sudhakar (Frontiers in Environmental Science, 2018)
Arsenic (As) contamination is a serious issue throughout the world. The scale of problem is being realized to be even greater with the discovery of new As contaminated regions with time. Rice is a staple crop across the world with approximately half of the world population dependent on rice for their daily dietary intake especially in Southeast Asian countries. It is not only the consumption of rice grains but also food products based on rice, which contribute towards As exposure to humans. Plant growth promoting microorganisms (PGPMs) constitute a diverse group of microorganisms including bacteria, fungi and microalgae. These are associated with the rhizospheric zone of plants. They improve plant growth through different mechanisms like increase of nutrients level in plants, improved soil quality, siderophore and hormone production, changes in biochemical properties of plants etc. Another important assistance imparted by PGPMs is the altered speciation of As in the soil through methylation and subsequent change in the bioavailability of As to the plants. Further, a change in As speciation also affects As uptake and transport in plants. The purpose of this review is to discuss importance of PGPM association in As toxicity amelioration in plants along with favourably reducing As concentrations in crop plants or increasing As accumulation in phytoremediator plants. This review also presents mechanisms of action of PGPMs and describes both laboratory- and field-studies on the application of PGPMs for tackling As-contamination. The future prospects of successful utilization of PGPMs are also discussed.